New alternative agents in essential tremor therapy: double-blind placebo-controlled study of alprazolam and acetazolamide - BEKİROĞLU, GÜLNAZ NURAL (SPRINGER-VERLAG, 2000)
Propranolol and primidone are widely used, effective agents in essential tremor although they are not tolerated by all patients. In the present study, the effectiveness of alprazolam, a triazole analog of benzodiazapine class, and acetazolamide, a carbonic anhydrase inhibitor, were investigated as symptomatic treatments for essential tremor. We studied 22 patients with essential tremor in a double-blind, cross-over, placebo-controlled design. The patients received in random order alprazolam, acetazolamide, primidone and placebo for four weeks, each separated by a two-week washout period. The study demonstrated that alprazolam was superior to placebo and equipotent to primidone, whereas there was no statistically significant difference between acetazolamide and placebo. The mean effective daily dose of alprazolam was 0.75 mg and there was not any troublesome side effect reported by the patients on alprazolam. Alprazolam can be used as an alternative agent in elderly essential tremor patients who can not tolerate primidone or propranolol.
Keywords: essential tremor therapy; alprazolam; acetazolamide; elderly; PRIMIDONE; EFFICACY; TRIAL